Avaliação do consumo específico de pó fluxante e sua correlação com os parâmetros do lingotamento contínuo de placas - Rodrigo Seara Martins (2019)
Mold powders are in continuous development to allow the continuous casting process to manufacture products with high surface quality. However, the selection and evaluation of the industrial performance of this raw material is not easy because it involves the simultaneous knowledge of its several properties. In this sense, since properly measured, the mold powder consumption in the mold can be a useful tool to evaluate the operational stability and the industrial performance of this raw material. There are several techniques and ways of evaluating the consumption of mold powder in the continuous casting process described in the literature. However, the correlation of consumption with process parameters depends on the particularity of each raw material and the characteristics of the process. Thus, the main motivation for the present project was to establish an accurate method to evaluate the performance of the mold powders in the mold of continuous casting, through measurements made with the mold flux used in the area and analyzes of the samples of powder in natura, liquid powder slag and powder slag film at the end of casting that will be collected during the accompanying series. The analyzes took into account the specific consumption and process parameters, seeking cause and effect relationships with events that may lead to deviations of the surface quality of the slab.The measurements of mold flux consumption performed with the new system designed in the presente work indicated that at Usiminas the process variable that had correlation with the mold powder consumption was the slab width.